2001
DOI: 10.1002/1097-0215(20010601)92:5<761::aid-ijc1238>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo documentation of photochemical internalization, a novel approach to site specific cancer therapy

Abstract: Photochemical internalization (PCI) is a unique procedure for site‐specific delivery of several types of membrane‐impermeable molecules to the cytosol of target cells. The technology is based on photochemical‐induced release of endocytosed macromolecules from endosomes and lysosomes into the cytosol. The purpose of this study was to evaluate the therapeutic potential of PCI of the type I ribosomal‐inactivating protein gelonin in an animal model. The photosensitizer aluminum phthalocyanine disulfonate (AlPcS2a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 37 publications
4
104
1
1
Order By: Relevance
“…This drug delivery system is based on photosensitizers that localize to the cells endosomes and lysosomes such as meso-tetraphenylporphine with 2 sulfonate groups on adjacent phenyl rings (TPPS 2a ) and aluminium phtalocyanine with two sulfonate groups on adjacent phthlates (AlPcS 2a ) (Berg et al 1990b, Berg & Moan 1994, Berg & Moan 1997, Selbo et al 2001b. These PSs are amphiphilic and are, upon administration, first adsorbed to the plasma membrane (Berg et al 1990b) before they are endocytosed into the membranes of the endocytic vesicles (Fig.4).…”
Section: The Principle Of Photochemical Internalizationmentioning
confidence: 99%
“…This drug delivery system is based on photosensitizers that localize to the cells endosomes and lysosomes such as meso-tetraphenylporphine with 2 sulfonate groups on adjacent phenyl rings (TPPS 2a ) and aluminium phtalocyanine with two sulfonate groups on adjacent phthlates (AlPcS 2a ) (Berg et al 1990b, Berg & Moan 1994, Berg & Moan 1997, Selbo et al 2001b. These PSs are amphiphilic and are, upon administration, first adsorbed to the plasma membrane (Berg et al 1990b) before they are endocytosed into the membranes of the endocytic vesicles (Fig.4).…”
Section: The Principle Of Photochemical Internalizationmentioning
confidence: 99%
“…6,7 Furthermore, the enhanced gene expression will only take place in tissue exposed to light, and thus the light treatment increases the specificity of the virus improving the therapeutic index. The PCI technology has already been implemented in animal models, and promising results have been obtained combining photochemical treatment with gelonin, a type I ribosomal-inactivating protein, 43 implying that the combination of adenoviral vectors and photochemical treatment has the potential to be successful in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The potentiating effects of PCI have previously been demonstrated in vitro (Engesaeter et al, 2006) and in vivo (Selbo et al, 2001;Dietz et al, 2005) and these results have been reviewed by Høgset (Høgset et al, 2004). While most studies have been carried out using amphiphilic photosensitisers (eg, TPPS 2a ) PCI has also been demonstrated using a membrane localising sensitiser, ALAinduced photoporphyrin IX.…”
Section: Photochemical Internalisationmentioning
confidence: 98%
“…While most studies have been carried out using amphiphilic photosensitisers (eg, TPPS 2a ) PCI has also been demonstrated using a membrane localising sensitiser, ALAinduced photoporphyrin IX. Selbo et al, 2001 administered the photosensitiser aluminium disulphonated phthalocyanine by intraperitoneal injection into athymic mice, followed (48 h later) by a single intratumoural injection of the protein toxin gelonin. The findings indicated that the photosensitiser could become localised in endosomes, in vivo, within the tumour cells and that upon illumination it could be relocalised to the cytoplasm.…”
Section: Photochemical Internalisationmentioning
confidence: 99%
See 1 more Smart Citation